Gender‐specific differences in parental health‐related quality of life in childhood cancer. Issue 7 (27th March 2019) - Rensen, Niki; Steur, Lindsay M.; Schepers, Sasja A.; Merks, Johannes H.; Moll, Annette C.; Kaspers, Gertjan J.; Grootenhuis, Martha A.; van Litsenburg, Raphaële R.
Abstract: Background: Parents of children with cancer are at risk for impaired health‐related quality of life (HRQoL). Most prior research has focused on the HRQoL of mothers. The aim of this study is to describe HRQoL in mothers and fathers, and determine the influence of sociodemographic, medical, and psychosocial factors. Procedure: In a cross‐sectional study, both parents completed questionnaires on sociodemographics, distress, and HRQoL. Parental HRQoL was compared to healthy population values. Differences between mothers and fathers were evaluated with multilevel analysis. Gender‐specific HRQoL determinants were assessed via multiple linear regression analysis. Results: Parents (202 mothers, 150 fathers; comprising 121 couples) of 231 children with different cancer diagnoses (mean time since diagnosis 3.3 ± 1.4 years, 90% posttreatment) participated. Compared to healthy women and men, mothers and fathers reported significantly impaired HRQoL on the following domains: cognitive functioning, sleep, daily activities, and vitality (Cohen's d  = 0.3‐0.9). Additionally, maternal HRQoL was reduced on the domains gross motor functioning, pain, social functioning, sexuality, and depressive emotions. Mothers scored worse than fathers on six of 12 domains. Risk factors for adverse outcomes in both parents were higher distress, emotional and parenting problems, little social support, medication use, and active treatment of the child. Other determinants in mothers were non‐Dutch background and unemployment, while lower HRQoL in fathers was predicted by their child's diagnosis type, shorter time since diagnosis, and treatment intensity. Conclusion: These outcomes illustrate the need for family‐centered care. Future interventions aimed at improving parental functioning should take into account gender‐specific differences in HRQoL to reach optimal efficacy.